How well do European loan markets work? Some insights from the financial structure of SMEs in three countries - Rien Wagenvoort; Christopher Hurst (EIB Papers, 1999)
The precarious employment situation in the EU has given rise to public policies that aim at giving small and medium-sized enterprises (SMEs) better access to finance. SMEs may face difficulties due to information problems and other inefficiencies in loan markets. However, the European evidence on the magnitude of this problem is limited. The purpose of this paper has been to explore the factors that determine the gearing of a sample of SMEs in France, Italy and the UK. Since many factors are potentially involved, a regression analysis is needed to untangle the individual effect of any particular factor. The explanatory power of our model is high compared with previous studies.
Keywords: 330; Klein- und Mittelunternehmen; Unternehmensfinanzierung; Fremdkapital; Kreditwürdigkeit; Kreditsicherung; Frankreich; Großbritannien; Italien